Leaving England : Essays on British Emigration in the Nineteenth Century - Erickson, Charlotte (Cornell University Press, 2019)
The British Isles provided more overseas settlers than any country in continental Europe during the nineteenth century, but English emigrants to North America have remained largely invisible, partly for lack of records about their departure or their experiences. Here Charlotte Erickson uses new sources to understand this long-neglected group and the nature of their lives in a new land.